Psychometric properties of the Malay translated Spielberger State-Trait Anxiety Inventory in exploring parental anxiety - Hashim Embong,; Wan Hasyila WO,; Ang, YH; Azlan Helmy AS,; Husyairi H, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
The aim of the study was to determine the psychometric properties of the Malay translated State-Trait Anxiety Inventory (STAI) for use in exploring the burden ofanxiety amongst parents of a child visited hospital for medical treatment. The instrument was administered to 53 parents of children seen in the Emergency Department and 52 parents in the outpatient Physiotherapy Unit. Internal consistency reliability (α) for state anxiety and trait anxiety subscale was high with values of 0.94 and 0.84, respectively. Test-retest reliability demonstrated wide range of scores with only 25 items showed significant intra-class correlation coefficients, ICC (range 0.60 – 0.94, 95% CI, p<0.05) after 4-weeks retest. Performances of matrix following a factor analysis were consistent with 4-factors structure of original STAI. A few items did not perform as expected but did not impair the overall performance. This Malay translated version is a valid and reliable measure of anxiety for parents with children visiting hospital for medical treatment, with caution in the interpretation of some items.